(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Fatty hepatosis (steatosis) is a condition characterized by the accumulation of fat in the liver, which can progress to non-alcoholic steatohepatitis, fibrosis, or cirrhosis. In recent decades, there has been a significant increase in the incidence of fatty hepatosis due to the rising prevalence of obesity, diabetes, and other metabolic disorders. Elastography, a non-invasive method for assessing liver stiffness using ultrasound, is becoming a key tool in the diagnosis and monitoring of fatty liver and hepatic fibrosis. This technique allows for the evaluation of liver damage without the need for invasive procedures such as biopsy.